Role of the chemokine receptor CCR5-dependent host defense system in Neospora caninum infections - Chisa Abe; Sachi Tanaka; Maki Nishimura; Fumiaki Ihara; Xuenan Xuan; Yoshifumi Nishikawa (Parasites & Vectors, 2015)
Abstract Background Neospora caninum, a Toxoplasma gondii-like obligate intracellular parasite, causes abortion in cattle and neurological signs in canines. To understand neosporosis better, studies on host cell migration and host immune responses during the early phase of infection are important. Although the C-C chemokine receptor 5 (CCR5) plays a crucial role in immune cell migration, the role played by it in protective immunity against N. caninum is poorly understood. Methods CCR5−/− mice were used to investigate their sensitivity levels to N. caninum infection and their ability to activate immune cells against this parasite. Results Increased mortality and neurological impairment were observed in the N. caninum-infected CCR5−/− mice. In comparison with wild-type mice, CCR5−/− mice experienced poor migration of dendritic cells and natural killer T cells to the site of infection. Dendritic cells in an in vitro culture from CCR5−/− mice could not be activated upon infection with N. caninum. Furthermore, higher levels of IFN-γ and CCL5 expression, which are associated with brain tissue damage, were observed in the brain tissue of CCR5−/− mice during the acute phase of the infection, while there was no significant difference in the parasite load between the wild-type and CCR5−/− animals. Additionally, a primary microglia culture from CCR5−/− mice showed lower levels of IL-6 and IL-12 production against N. caninum parasites. Conclusions Our findings show that migration and activation of immune cells via CCR5 is required for controlling N. caninum parasites during the early phase of the infection.